Cervical cancer screening practices in central and eastern Europe in 2012 - Maver Vodičar, Polona (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2013)
The burden of cervical cancer in central and eastern Europe is generally higher compared to western or northern Europe due to a history of mostly opportunistic cervical cancer screening practices and due to the strong influence of political and economic changes in post-communist transition. This article describes the current cervical cancer screening practices, organizational plans for the future, and main obstacles that need to be overcome in 16 countries in central and eastern Europe: Albania, Bosnia and Herzegovina, Bulgaria, Croatia, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Montenegro, Poland, Romania, Serbia, Slovakia, Slovenia and The former Yugoslav Republic of Macedonia. Unfortunately, only a few countries have managed to establish an organized and well-functioning cervical cancer screening program in recent years, whereas most countries in the region are still struggling with implementation-related issues of organized cervical cancer screening. Encouragingly, even in the countries where only opportunistic screening is performed, well-prepared plans and strategies have been established for switching to organized screening in the near future.
Keywords: centralna Evropa; diagnostika; Eastern Europe; maternični vrat; novotvorbe; presejanje; tumor; vzhodna Evropa